EFFECT OF INSURGENCY ON FOOD CROP PRODUCTION IN THE ARID AGRO-ECOLOGICAL ZONE: A CASE STUDY OF FIKA LOCAL GOVERNMENT AREA, YOBE STATE, NIGERIA - Kareto, B. A.; Aliyu, Y.M.; Thamus, Z.Y.; Mudi, Z.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the effect of insurgency on food crop production in the arid agro-ecological zone of Fika Local Government Area, Yobe State, Nigeria. Multistage sampling technique was used to select 390 respondents from the study area. Data were collected using structured questionnaires and analyzed using descriptive and inferential statistical tools. The results showed that majority (70%) of the farmers were male while 35.1% were within the economically active age bracket of 31–40 years, and 50% had moderate household sizes (5–8 members). Educational attainment was generally low, with 40% having no formal education. Farm sizes were predominantly small-scale (1–3 hectares), and 40% of respondents earned below ₦50,000 annually. Extension services and access to credit were limited, reaching only 40% and 30% of the farmers respectively. Respondents with the mean score (4.30) strongly agreed that insurgency led to reduced food crop production, farmland abandonment, inaccessibility of rural markets, loss of crops, increased food prices, reduced income, and widespread hunger. The results revealed that Hike in prices of commodities with mean score (4.50) strongly agree, social vices mean score (4.15) strongly agree respectively. The results further revealed that farmers adopted coping strategies such as backyard farming with the mean of (4.50) strongly agree, petty trading, reducing food quality and quantity with the mean sore (4.40) strongly agree. The results of regression analysis revealed that Age (P<0.01), education (P<0.01) farm size (P<0.01) and income (P<0.01) influenced the impact of insurgency on food crop production. The study concludes that insurgency has deeply disrupted food crop production in Fika LGA, worsening food insecurity and economic vulnerability in the arid region. The study recommends increased government investment in agricultural extension, rural credit, infrastructure, and education, alongside strengthened security and peacebuilding interventions. Promoting resilient livelihood strategies and alternative income sources is also vital to reduce.